Analysis of the main approaches to the treatment of subjective well-being in psychology - Khaleeva, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article analyzes the basic theory of subjective well-being. It is indicated that the desire for well-being is one of the main driving forces of human society, its subjective feeling is an important condition for a full-fledged life of a person, therefore, attention is drawn to the need for psychological research related to the analysis of methodological and systemic approaches aimed at studying subjective well-being. The main differences between the theories, as well as the relationship between the concepts of "well-being", "subjective well-being" and "psychological well-being" are shown, a theoretical analysis of existing modern approaches to the problem of studying subjective well-being and its components is carried out. Subjective well- being is considered as an integral psychological formation, including the assessment and attitude of a person to his life and himself. The main approaches to elucidating the components of subjective well-being are characterized – hedonistic and eudemonistic. Based on the analysis of modern and research, a study of its sources and determinants is carried out, the component composition, terminology base is clarified, the influence of various factors, such as: social relations, genetic predisposition, material well-being, joy of needs, existence of goals and meaning of life, physical activity are investigated , individual characteristics, accepting oneself as a person, etc. Through a synthesis of various approaches to understanding subjective well-being, several key statements have been identified in the framework of the study: the positivity of measuring well-being as the presence of positive intensity indicators and experiences of different intensities; global dimension – the interconnection of all aspects of human life (social, biological, psychological, physical) time lag, dynamism; subjectivity as the dependence of the experience of well-being on assessment, attitude and personal experience. Attention is drawn to the fact that the term "subjective well-being" is interdisciplinary and has its meaning in psychology, sociology, economics and the political sciences. The prospect of further research is seen in continuing to study the structural features of models and components of well-being.